Allophonic tunes of contrast: Lab and spontaneous speech lead to equivalent fixation responses in museum visitors. Issue 1 (4th April 2017) - Ito, Kiwako; Turnbull, Rory; Speer, Shari R.
Abstract : A prominent pitch accent is known to trigger immediate contrastive interpretation of the accented referential expression. Previous experimental demonstrations of this effect, where [L+H* unaccented] contours led to an increase in earlier responses than [H* !H*] contours in contrastive context, may have benefited from the use of laboratory speech with stylized, homogenous pitch contours as well as data collected from a uniform participant group—college students. The present study tested visitors to a science museum, who better represent the general public, comparing lab and spontaneous speech to replicate the contrast-evoking effect of prominent pitch accent. Across two eye-tracking experiments where participants followed spoken instructions to decorate Christmas trees, spontaneous two-word [L+H* unaccented] contours led to faster eye-movements to contrastive ornament sets than [H* !H*] contours with no delay as compared to lab speech. The differences in the fixation functions were overall smaller than those in a previous study that used clear lab speech in richer contexts. Detailed acoustic analyses indicated that the lab speech tune types were distinguishable by any of several independent F0 measures on the adjective and by F0 slope. In contrast, no single phonetic measure on the spontaneous speech adjective distinguished between tune types, which were best classified according to independent noun-based measures. However, a non-linear combination of the adjective measures was shown to be equal to the noun measures in distinguishing between the [H* !H*] and [L+H* unaccented] tunes. The eye-movement data suggest that naïve listeners were comparably sensitive to both lab and spontaneous prosodic cues on the adjective and made anticipatory eye-movements accordingly.